Mobile complex of equipment for 3D printing (Academic journal Industrial Machine Building Civil Engineering, 2023)
The research explores the possibility of using mobile 3D printing technologies in construction and manufacturing. It is noted that many equipment manufacturers are already utilizing 3D printing for constructing various objects, but one of the limitations has been the lack of mobility. However, new concepts and prototypes of mobile 3D printers are emerging, which allow for construction and manufacturing in different locations without the need for additional transportation equipment. The proposed design of a mobile 3D construction printer-complex, housed on a cargo semi-trailer, is suggested as a mobile and autonomous system for construction purposes.
Keywords: additive manufacturing; 3D printing; robotic printers; concrete printing; concrete mixture; vibrator